2012
DOI: 10.1038/labinvest.2012.60
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia and xerostomia are key determinants of tooth decay in type 1 diabetic mice

Abstract: Insulin-dependent type 1 diabetes mellitus (DM) and oral diseases are closely interrelated. Poor metabolic control in diabetics is associated with a high risk of gingivitis, periodontitis and tooth loss. Salivary flow declines in diabetics and patients suffer from xerostomia. Reduced saliva predisposes to enamel hypomineralization and caries formation; however, the mechanisms that initiate and lead to progression of tooth decay and periodontitis in type 1 DM have not been explored. To address this issue, we an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 56 publications
4
40
0
2
Order By: Relevance
“…Even if the association between these variables did not show significant results, it is suggested a relationship with dysfunction of salivary secretion resulting from this situation. Of the sample, 54.5% exhibited decreased salivary flow, even that the association of dry mouth and saliva amount (p=0.076) and stimulated saliva (p=0,067) did not show statistically differences, corroborating the literature [4,7,11,17,19,23,26]. Although further studies with larger samples should be conducted in the search for meaningful results, the relationship between the dentist and doctor is necessary, and the medical history of the patient is essential for diagnosis and best treatment in situations of hyposalivation and xerostomia.…”
Section: Discussionsupporting
confidence: 82%
“…Even if the association between these variables did not show significant results, it is suggested a relationship with dysfunction of salivary secretion resulting from this situation. Of the sample, 54.5% exhibited decreased salivary flow, even that the association of dry mouth and saliva amount (p=0.076) and stimulated saliva (p=0,067) did not show statistically differences, corroborating the literature [4,7,11,17,19,23,26]. Although further studies with larger samples should be conducted in the search for meaningful results, the relationship between the dentist and doctor is necessary, and the medical history of the patient is essential for diagnosis and best treatment in situations of hyposalivation and xerostomia.…”
Section: Discussionsupporting
confidence: 82%
“…It is, however, common in those suffering from type 1,2 diabetes (27)(28). Dry mouth may be caused as a side effect of medication that is being consumed to keep the diabetes in control.…”
Section: Diabetesmentioning
confidence: 99%
“…Akita mice are hyperglycemic with a bone loss skeletal phenotype being more severe in male offsprings of diabetic fathers [166]. Previous studies also revealed that Akita mice have decreased anabolic response in bone formation upon mechanical loading, revealing altered osteoblast response in bone reponse to loading [167], as well as having chalky white incisors with decreased enamel mineralization [168]. The Akita mice have an osteoporotic bone phenotype similar to patients with T1DM, and in comparison have a less severe osteoporotic bone phenotype compared to the drug induced diabetic mouse model, Streptozotocin (STZ) mice [52].…”
Section: Introductionmentioning
confidence: 99%